Polyamines regulate their synthesis by inducing expression and blocking degradation of ODC antizyme - Palanimurugan, R (Nature Publishing Group, 2004)
Polyamines are essential organic cations with multiple cellular functions. Their synthesis is controlled by a feedback regulation whose main target is ornithine decarboxylase (ODC), the rate-limiting enzyme in polyamine biosynthesis. In mammals, ODC has been shown to be inhibited and targeted for ubiquitin-independent degradation by ODC antizyme (AZ). The synthesis of mammalian AZ was reported to involve a polyamine-induced ribosomal frameshifting mechanism. High levels of polyamine therefore inhibit new synthesis of polyamines by inducing ODC degradation. We identified a previously unrecognized sequence in the genome of Saccharomyces cerevisiae encoding an orthologue of mammalian AZ. We show that synthesis of yeast AZ (Oaz1) involves polyamine-regulated frameshifting as well. Degradation of yeast ODC by the proteasome depends on Oaz1. Using this novel model system for polyamine regulation, we discovered another level of its control. Oaz1 itself is subject to ubiquitin-mediated proteolysis by the proteasome. Degradation of Oaz1, however, is inhibited by polyamines. We propose a model, in which polyamines inhibit their ODC-mediated biosynthesis by two mechanisms, the control of Oaz1 synthesis and inhibition of its degradation.